Sequence-Tagged Site of Defense-Related Genes for Resistant/ Susceptible Eucalypt Selection to Cryptosporiopsis eucalypti - Yuttana Singchada; Saowanee Suputtitada; Poonpilai Suwanarit; Somsak Apisitwanich (Agriculture and Natural Resources, 2006)
Leaf spot and shoot blight caused by the fungal pathogen, Cryptosporiopsis eucalypti, is the most severe disease for eucalypt plantation in Thailand. The objective of this study was to create a set of DNA markers for resistant clone detection. Twelve clones of eucalypt were selected and screened for disease resistance using intact seedling inoculation and detached leaf techniques in the greenhouse and laboratory. Six clones, SF01, SF06, SF18, SF36, SF94 and SF98, were classified as resistance while the other six, SF03, SF07, SF14, SF16, SF70 and SF86, were susceptible clones. The sequence-tagged-site (STS) marker of pathogenesis-related (PR) genes, plant disease resistance (R) genes, and defense-related genes were analyzed in both DNAs of resistant and susceptible groups using polymerase chain reaction (PCR). Amplified DNA fragments were separated by agarose gel and polyacrylamide gel electrophoresis. The results showed that six markers (Ce1, Ce2, Ce3, Ce4, Ce5 and Ce6) from thirty five primer pairs could be used for susceptible and resistant detection of eucalypt.